Screening commonly cultivated rice cultivars in Sri Lanka with special reference to Jaffna for salt tolerance at seedling stage under hydroponics - Pradheeban, L.; Nissanka, S.P.; Suriyagoda, L.D.B. (International Journal of Agronomy and Agricultural Research (IJAAR), 2015)
To screen rice cultivars cultivated in Sri Lanka for salt tolerance at seedling stage, factorial experiment was conducted in a completely randomized design with five replicates. Twenty two rice cultivars were tested against five salt levels (0, 4, 8, 12 and, 24 dSm-1). Using shoot, root parameters and its percentage reduction with salt levels and sodium to potassium ratio, grouping of rice cultivars and their significances were tested by using cluster analysis. Four groups were identified as; highly tolerant, tolerant, susceptible and very susceptible. ANOVA and correlation analysis were performed to check the significant differences among cultivars with in clusters and correlation between tested variables, respectively. Values of all tested variables decreased with increasing salt levels in all tested cultivars except for sodium to potassium ratio in shoots. Percentage reduction increased with increasing salt levels for shoot height, shoot dry weight, root length, root dry weight and root surface area and showed significant differences among the cultivars at salt level of 24 dSm-1 . Both osmotic and toxic effect reduced shoot and root growth by inhibiting the water absorption by roots and caused leaf death, respectively. Among the cultivated rice cultivars, based on shoot and root parameters and sodium to potassium ratio in shoots, Pachaperumal, Periavellai, At 303, Adakari, Bg 406 and CO 10 categorized as highly tolerant group while Bg 250, At 353, At 362, Modaikarupan, H4, Bg 304 and Morungan were grouped as tolerant. Also Bg 352 and At 308 found susceptible and Bg 360 seems very susceptible.
Keywords: Hydroponics; Jaffna; Rice; Seedling; Sodium chloride